Kontrol Kestabilan Kapal Autonomous Submarine Surface Vehicle Dengan Metode Fuzzy logic - Abdul Hafizh Abyan Faruq; Joko Endrasmono; Isa Rachman; Agus Khumaidi; Ryan Yudha Adhitya; Zindhu Maulana Ahmad Putra (Infotekmesin, 2023)
The Autonomous Submarine Surface Vehicle is a type of unmanned underwater vehicle. When the ship performs maneuvers, there are large Pitch and Roll motions. This research aims to control the stability of the Autonomous Submarine Surface Vehicle with Fuzzy. The first process is taking Pitch and Roll data followed by the Fuzzification process to change input data with firm values into Fuzzy values. The next stage is Inference by using the rules (if – then) and the Deffuzification process to change the results of the inference stage into output values. The last is the process of stabilizing the ship with a Thruster dc motor. When the system is activated, it has a time of 0.518 seconds faster to steady state than the deactivated system with a roll tilt of (plus) 11°. On the roll tilt of (plus) 20° the highest PWM rotation is 1600µs with a time of 9,342 seconds to steady state and the roll tilt is (plus) 11° with the highest PWM of 1500µs with a time of 4,335 seconds. Based on this research, the Fuzzy Method can control the stability of the Autonomous Submarine Surface Vehicle ship.